Infantile epileptic spasm syndrome: predictors of short- and long-term outcomes - Al-Omari, Mohammed A.; Chavez-Castillo, Melissa; Miller, Michael R.; Prasad, Asuri N.; Nouri, Maryam Nabavi (Frontiers in Pediatrics, 2025)
IntroductionInfantile epileptic spasm syndrome (IESS) has significant impact on affected children that affects their future seizure control and neurodevelopmental outcomes. The aim of this study is to identify potential short- and long-term predictors of outcomes in children diagnosed IESS.MethodThis retrospective study evaluated outcomes of seizure control and developmental status in a historical cohort of 60 children with IESS. The predictor variables included: age, treatment regimen, and early treatment response at 14 days, 3 and 6 months on the measured outcomes.ResultsAmong the 60 children in the cohort, 75% had identified etiologies: Genetic (40%), Structural (35%), and unknown causes (25%). Treatment interventions included either vigabatrin monotherapy (58.33%) or hormonal therapy with or without vigabatrin (41.67%). Clinical response at 3 and 6 months significantly correlated with good seizure control (p = 0.008 and p = 0.007, respectively) and favorable developmental outcome (p < 0.001) at last follow-up. Logistic regression showed that treatment response at 3 months increased the odds of good seizure control by 7.21 times (95%CI = 1.93–26.91, p = 0.003), after adjusting for age, treatment regimen, and etiology. Genetic and structural etiologies were significantly associated with a higher likelihood of developing epileptic encephalopathy (EE), with odds ratios of 11.79 (95% CI = 2.04–68.06, p = 0.006) for genetic etiology and 10.21 (95% CI = 1.75–59.65, p = 0.010) for structural etiology.DiscussionEarly treatment response at 3 and 6 months strongly predicts favorable seizure and developmental outcomes in IESS, with poor responders at these time points more likely to develop EE. Genetic and structural etiologies significantly influence EE risk, emphasizing the need for early identification, sustained treatment monitoring, and potential targeted interventions for high-risk subgroups.